STUDI KTIRIS PRAKTIK DOKTEROID PARAMEDIS PADA PELAYANAN KESEHATAN - Siti Soekiswati (Media Keadilan: Jurnal Ilmu Hukum, 2019)
The chaotic health services due to paramedical doctoroid practices have an impact on legal and humanitarian issues. The existence of violation of the law by paramedic doctoroid actors is inseparable from the weakness of the legal system and structure in the world of medical health. This study aims to uncover paramedics who practice doctoroid practice on independent practice. Using the type of sociological legal research (sociolegal-research) that is descriptive analytical, with a critical study approach. Analysis of the results of the study showed that the practice of paramedic physoids was caused by the legal system starting from the substance of the law, legal structure and pathological legal culture. The types of physician practices carried out by paramedics include the practices of the authority of general practitioners, pediatricians, gynecologists, internists, cardiologists, dermatologists, surgeons and dentists. Doctoroid practice is a sub-standard health service which is actually a form of violation of the law in medical practice. Based on these conditions, then the form of transcendental-based legal protection as a solution. Transcendental-based legal protection is a preventive legal protection aimed at establishing a true legal perspective as a result of the process of internalizing divine revelation which is then objectified in the character of legal actors.Keywords: legal protection, paramedic doctoroid practice, transcendentalABSTRAKCarut marutnya pelayanan kesehatan akibat praktik dokteroid paramedis berdampak kepada persoalan hukum dan kemanusiaan. Adanya pelanggaran hukum oleh pelaku dokteroid paramedis tidak terlepas dari lemahnya sistem dan struktur hukum yang ada di dunia kesehatan medis. Penelitian ini bertujuan untuk mengungkap paramedis yang melakukan praktik dokteroid pada praktik mandiri. Menggunakan jenis penelitian yuridis sosiologis (sociolegal-research) yang bersifat deskriptif analitis, dengan pendekatan studi kritis. Analisis dari hasil penelitian menunjukkan bahwa praktik dokteroid paramedis disebabkan karena sistem hukum mulai dari substansi hukum, struktur hukum dan budaya hukum yang patologis. Jenis praktik dokter yang dilakukan oleh paramedis, berupa praktik kewenangan dokter umum, spesialis anak, ginekologis, internis, cardiologis, dermatologis, spesialis bedah maupun dokter gigi. Praktik dokteroid merupakan pelayanan kesehatan substandar yang sebenarnya adalah bentuk pelanggaran hukum dalam praktik kedokteran. Atas dasar kondisi tersebut, maka bentuk perlindungan hukum berbasis transendental sebagai solusi. Perlindungan hukum berbasis transendental merupakan perlindungan hukum preventif bertujuan terbentuknya perspektif hukum yang benar sebagai hasil proses internalisasi wahyu ilahiah yang kemudian terobjektifikasi dalam karakter para pelaku hukum.Kata Kunci: perlindungan hukum, praktik dokteroid paramedis, transendental